2022
DOI: 10.1111/jbi.14464
|View full text |Cite
|
Sign up to set email alerts
|

Genetic impacts of physical disturbance processes in coastal marine ecosystems

Abstract: Aim Coastal habitats are among the most dynamic environments on earth and are highly vulnerable to large‐scale physical disturbance. Genetic studies of nearshore marine species are revealing long‐lasting signatures of major coastal disturbance events. We synthesize emerging data to highlight how physical perturbations can impact the phylogeographic patterns of coastal populations. Taxon Coastal marine and estuarine taxa. Location Coastal regions around the globe. Methods We synthesize coastal genetic and genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 169 publications
0
7
0
Order By: Relevance
“…Major tropical hurricanes, such as Irma and Maria, are capable of modifying coastal and nearshore physical landscapes, affecting the genetic diversity and population structure of coastal marine species (Apodaca et al., 2013; Banks et al., 2013; Pagán et al., 2020; Parvizi et al., 2022). Some of these changes arise from altering habitat suitability and availability of substrate for larval settlement (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Major tropical hurricanes, such as Irma and Maria, are capable of modifying coastal and nearshore physical landscapes, affecting the genetic diversity and population structure of coastal marine species (Apodaca et al., 2013; Banks et al., 2013; Pagán et al., 2020; Parvizi et al., 2022). Some of these changes arise from altering habitat suitability and availability of substrate for larval settlement (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings differ from prior genetic analysis using only conservative mitochondrial and plastid molecular markers that revealed negligible genetic diversity among the population in Tasmania (Macaya & Zuccarello, 2010, Durrant et al ., 2015). A genome-wide approach is more powerful in revealing fine-scale intraspecific structures (Parvizi et al ., 2022). Distinct genetic structuring using nuclear microsatellite loci (Alberto et al ., 2009) has, however, been observed in population genetic analyses of M. pyrifera in the northeastern and southeastern Pacific (Alberto et al ., 2010, Johansson et al ., 2015, Camus et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale mortality of intertidal and subtidal communities as a result of tectonically uplifted shoreline has been widely recorded in central-southern Chile (Castilla, 1988;Castilla et al, 2010;Jaramillo et al, 2012). Local/regional extirpations followed by recolonizations from sources populations not necessarily located nearby can lead to genetic anomalies that present the same signature as classical phylogeographic breaks but are not linked to the existence of any barrier to gene flow (Parvizi et al, 2019;Vaux et al, 2021;Parvizi et al, 2022;Vaux et al, 2022;Vaux et al, 2023). In Chile, it has been shown that regional disturbance events can rapidly reshape the pattern of distribution of genetic diversity in coastal species (Brante et al, 2019;Becheler et al, 2020).…”
Section: Shallow and Taxa Dependent Genetic Sub-structuring Patterns ...mentioning
confidence: 99%